Management Consulting: A Guide to the Profession - Milan Kubr; Martin Kubr (USA International Labor Office, 2003)
Widely recognized as a key reference work on the practice of consulting, this guide offers an extensive introduction to professional consulting, its nature, methods, organizational principles, behavioral rules, and training and development practices. Today's information- and knowledge-based economy is constantly creating new opportunities and challenges for consultants. This new edition of Management Consulting actively reflects and confronts these developments and changes. New topics covered in this edition include: e-business consulting consulting in knowledge management total quality management corporate governance social role and responsibility of business company transformation and renewal public administration This book serves as a useful and inspiring tool for individuals and organizations wishing to improve their consulting activities.
Keywords: Business; Management; Consulting; Textbooks; Enterprise and Practice (BIN2045-N)